Cheese and Healthy Diet: Associations With Incident Cardio-Metabolic Diseases and All-Cause Mortality in the General Population - Dekker, Louise H.; Vinke, Petra C.; Riphagen, Ineke J.; Minović, Isidor; Eggersdorfer, Manfred L.; van den Heuvel, Ellen G. H. M.; Schurgers, Leon J.; Kema, Ido P.; Bakker, Stephan J. L.; Navis, Gerjan (Frontiers in Nutrition, 2019)
Background: Many countries have established Food-Based Dietary Guidelines (FBDG).. For some foods, such as cheese, there is no consensus on whether or not to include them in these guidelines. Cheese may, however, be an excellent source of vitamin K2, which is a macronutrient with demonstrated positive results on cardiovascular-related outcomes. Aim: First, we assessed the role of cheese within the recently developed Lifelines Diet Score (LLDS), a score based on the Dutch FBDG 2015 in relation to incident cardio-metabolic diseases and all-cause mortality. Secondly, we assessed the association of cheese intake with desphospho-uncarboxylated matrix Gla protein (dp-ucMGP), a marker for functional vitamin K2 status, in a subset of the population. Methods: From the Lifelines cohort study, 122,653 adult participants were included to test the association between de LLDS and health outcomes. In a subset of 1,059 participants aged 60-75 years, dp-ucMGP levels were measured. Dietary intake was assessed using a 110-item Food Frequency Questionnaire. Logistic regression were applied, adjusted for relevant confounders. Results: Median cheese intake was 23.5 [12.6-40.6] g/day. We found a positive correlation between cheese intake and the LLDS (Spearman’s rho = 0.024, p<0.001). The LLDS in quintiles was associated with T2DM (OR [95% CI] Q5 [healthy diet] vs Q1 [poor diet] = 0.54 [0.43-0.67]) and all-cause mortality (Q5 vs. Q1 = 0.62 [0.50-0.76]). Inclusion of cheese did not alter these associations. Additionally, we found no significant association of total cheese intake with plasma dp-ucMGP levels. Conclusion: In this population-based cohort study, the inclusion of cheese in the LLDS did not change the inverse associations with incident cardio-metabolic diseases and all-cause mortality. Furthermore, we found no significant association of total cheese intake with plasma dp-ucMGP. The results suggest that cheese is a neutral food group that fits a healthy diet